Does Scalp Cooling Have the Same Efficacy in Black Patients Receiving Chemotherapy for Breast Cancer?. (17th February 2021) - Dilawari, Asma; Gallagher, Christopher; Alintah, Princess; Chitalia, Ami; Tiwari, Shruti; Paxman, Richard; Adams‐Campbell, Lucile; Dash, Chiranjeev
Abstract: Lessons Learned: Despite U.S. Food and Drug Administration approval to reduce alopecia, data on efficacy of scalp cooling in Black patients with cancer are limited by lack of minority representation in prior clinical trials. Scalp cooling devices may have less efficacy in Black patients; additional studies are required to explore the possible causes for this, including hair texture and cap design. Background: The Paxman scalp cooling (SC) device is U.S. Food and Drug Administration (FDA)‐approved for prevention of chemotherapy‐induced alopecia. Studies report 50%–80% success rates and high patient satisfaction, yet there have been no studies of SC in Black patients. We conducted a phase II feasibility study of Paxman SC with a planned enrollment of 30 Black patients receiving chemotherapy for stage I–III breast cancer. Methods: Black patients who planned to receive at least four cycles of chemotherapy with non‐anthracycline (NAC) or anthracycline (AC) regimens were eligible. Alopecia was assessed by trained oncology providers using the modified Dean scale (MDS) prior to each chemotherapy session. Distress related to alopecia was measured by the Chemotherapy Alopecia Distress Scale (CADS). Results: Fifteen patients enrolled in the intervention before the study was closed early because of lack of efficacy. Median MDS and CADS increased after SC, suggesting increased hair loss ( p < .001) and alopecia distress ( p = .04). Only one participant was successful in preventing significant hair loss; the majority stopped SC before chemotherapy completion because of grade 3 alopecia (>50% hair loss). Conclusion: SC may not be efficacious in preventing alopecia in Black women. Differences in hair thickness, hair volume, and limitations of cooling cap design are possible contributing factors.